A model for teacher training in artificial intelligence and learning analytics for course design in Moodle - Columba Tibanta, Diego; López Fernández, PhD. Raúl; Tapia Bastidas, PhD. Tatiana (Revista Minerva, 2025)
The process of continuous teacher training is an interest of any educational system and if it is based on technological developments such as artificial intelligence (AI), learning analytics (LA) and Moodle course design, it becomes even more relevant. The objective of this research was to develop a model for training teachers in artificial intelligence (AI), learning analytics (LA) and Moodle course design to be applied in their teaching practice. For this purpose, the theoretical, historical-logical and inductive-deductive methods were used. From the empirical point of view, diagnosis, a semi-structured interview, modeling, expert criteria and Regnier's abacus were used. The results obtained were the development of a training model applicable and contextualizable to the pedagogical practice of each teacher, with the advantage that it can be adapted and improved depending on their training needs. It is concluded that IA and AA tools are fundamental in the design of virtual courses that must be designed, organized and executed by the teachers to whom they are addressed, and another important element is that those involved can become multipliers in the application of the model.
Keywords: learning analytics; training; artificial intelligence; moodle